2012
DOI: 10.1111/j.1600-6143.2012.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Graft Dysfunction After Living Donor Liver Transplantation Is Characterized by Delayed Functional Hyperbilirubinemia

Abstract: The purpose of this study is to propose a new concept of primary graft dysfunction (PGD) after living donor liver transplantation (LDLT), characterized by delayed functional hyperbilirubinemia (DFH) and a high early graft mortality rate. A total of 210 adult-to-adult LDLT grafts without anatomical, immunological or hepatitisrelated issues were included. All of the grafts with early mortality (n = 13) caused by PGD in LDLT had maximum total bilirubin levels >20 mg/dL after postoperative day 7 (p < 0.001). No ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 32 publications
(50 reference statements)
1
63
1
Order By: Relevance
“…It is well accepted that the graft quality, including the graft size and the donor age, and the recipient condition, including the patient status, the MELD score, and the extent of portal hypertension, are determinants of recipient outcomes . We previously reported that advanced donor age, recipient hospitalization, and high MELD scores were among the risk factors for postoperative primary graft dysfunction with severe hyperbilirubinemia . In the current study, all of the donors for the elderly recipients were their children.…”
Section: Discussionmentioning
confidence: 67%
“…It is well accepted that the graft quality, including the graft size and the donor age, and the recipient condition, including the patient status, the MELD score, and the extent of portal hypertension, are determinants of recipient outcomes . We previously reported that advanced donor age, recipient hospitalization, and high MELD scores were among the risk factors for postoperative primary graft dysfunction with severe hyperbilirubinemia . In the current study, all of the donors for the elderly recipients were their children.…”
Section: Discussionmentioning
confidence: 67%
“…This syndrome is defined as delayed functional hyperbilirubinemia: total serum bilirubin > 20 mg/dL for >7 consecutive days occurring after the 7th POD, excluding technical, immunological, and hepatitis factors. [17] …”
Section: Methodsmentioning
confidence: 99%
“…Patients with (i) recent acute cellular rejection or hepatic decompensation, (ii) Hb less than 10.0 g/L, (iii) eGFR (mL/min/1.73 m 2 ) of 0.808 (coefficient for Japanese population) Â 175 Â serum creatinine j1.154 Â age j0.203 Â 0.742 (if female) (25), or (iv) nonYgenotype 1 HCV were ineligible for triple antiviral therapy. The surgical procedures used for the donors and recipients are described elsewhere (26). In our institute, splenectomy is performed in recipients with hepatitis C to prevent pancytopenia during antiviral therapy (27).…”
Section: Patientsmentioning
confidence: 99%